Erosive oral lichen planus with cutaneous involvement in a 7-year-old girl: A rare case report - Ganapathi Moger; Chandrashekar K Thippanna; Mallikarjun Kenchappa; Vinuth D Puttalingaiah (Wolters Kluwer Medknow Publications, 2013)
Lichen planus is a chronic autoimmune, mucocutaneous disease, which can affect the oral mucosa, skin, genital mucosa, scalp and nails, and commonly seen in adults. Childhood lichen planus is a rare entity, which is characterized by skin lesions with the oral involvement being extremely uncommon. There are only a few reports on this subject in the literature. Early and correct diagnosis with adequate management is very important to avoid further complications as it is a pre-malignant condition. Herewith, we report a seven-year-old girl having erosive oral lichen planus with cutaneous involvement, which responded well to the treatment. This is to add another case of lichen planus in a child and to emphasize its consideration in the differential diagnosis of oral mucosal red and white lesions in children.